Nursing care of an indigenous patient in intensive care at a federal university hospital: experience report (Research, Society and Development, 2022)
This article aims to report the experience lived by a nurse in the care of an indigenous patient, in the Intensive Care Unit of a Federal University Hospital in the State of Pará. This is a qualitative, descriptive, experience report type study. Communication was the point of difficulty encountered by nursing in interacting with the indigenous patient, evidenced at the time of patient admission to the Intensive Care Unit. The nurse's perception of involving the companion who was fluent in Portuguese was important for the success of the treatment. It was evident that, currently, when talking about assistance to indigenous patients, nursing perceives that there is a need for investment in the qualification of health professionals, since care is still permeated by stigma and based on personified and individual treatment. Therefore, the qualification of professionals must involve reception, guaranteeing access and comprehensive care that is provided to indigenous peoples.